Pre-exposure prophylaxis use among HIV serodiscordant couples: a qualitative study in Mozambique. Issue 1 (1st January 2021) - Sack, Daniel E.; De Schacht, Caroline; Paulo, Paula; Graves, Erin; Emílio, Almiro M.; Matino, Ariano; Fonseca, Carlota L.; Aboobacar, Arifo U.; Van Rompaey, Sara; Audet, Carolyn M.
ABSTRACT: Background: Pre-exposure prophylaxis (PrEP) has the potential to reduce HIV transmission and stem the HIV epidemic. Unfortunately, PrEP uptake in rural sub-Saharan Africa has been slow and medication adherence has been suboptimal. Objective: To explore the perspectives, attitudes, and experiences of HIV serodiscordant partners taking PrEP and develop a messaging campaign to improve PrEP uptake in rural Mozambique to reduce HIV transmission among serodiscordant partners. Methods: In this qualitative study, we interviewed 20 people in serodiscordant relationships using PrEP at a rural health center in Zambézia province, Mozambique and employed inductive and deductive coding to elicit their perspectives, attitudes, and experiences related to learning their partner's HIV status, barriers to PrEP uptake, obstacles to PrEP adherence, and decisions to disclose their PrEP use with family and friends using thematic analysis. Results: Our analysis generated nine themes across various levels of the socioecological model. Participants reported a strong desire to stay in the discordant relationship and highlighted the importance of working together to ensure PrEP and antiretroviral therapy adherence, with the majority skeptical that adherence could be achieved without both partners' support (individual and interpersonal). Although most participants were reticent about sharing their serodiscordant status with family and friends (individual and interpersonal), those who did found their family and friends supportive (interpersonal). Participants suggested increasing community health agent availability to help people navigate HIV prevention and treatment (organizational). We then created three oral stories, using themes from the interviews, with examples from various levels of the socioecological model that will be used to generate support for PrEP use among community members. Conclusions: Our findings informed oral template stories that will be used to emphasize how couples can work together to improve PrEP uptake and reduce incident HIV infections in serodiscordant couples elsewhere in rural Mozambique.